Estudo envolvendo o armazenamento de combustíveis gasosos na forma adsorvida à baixa pressão - Marins, Daniel Sena (2023)
Natural Gas storage technology using adsorbent materials (Adsorbed Natural Gas - ANG) has been emerging in recent years as it is considered a promising alternative between compression and liquefaction technologies. Based on the adsorption of gas in porous solids under moderate pressure, the ANG makes it possible to make storage and distribution operations more flexible and to diversify units and gas supply systems to reduce costs. In view of this, this work aims to evaluate the storage capacity of gaseous fuels in the form adsorbed on porous carbon-based solids using a laboratory scale prototype. The ability to store gaseous fuels chemically composed of CH4, CO2 and H2 in the form adsorbed on babassu bark activated charcoal (8x30) was determined under different temperature conditions. Activated carbon was characterized by X-ray diffraction (XRD), N2 and CO2 physisorption, scanning electron microscopy with Energy Dispersive Spectroscopy (SEM - EDS), absolute density and absorption spectroscopy in the infrared region with Fourier Transform (FTIR). The analyzes indicated that activated carbon has a high absolute density and morphological structure with high heterogeneity, considerable surface area for GNA applications (584 m2 g-1) with a microporous structure (322 m2 g-1). The results showed that the storage capacity of CH4 and CO2 (without mixtures) in the adsorbed form is higher than in the compressed form up to 35 bar and that the temperature variation (ΔT = 25°C) directly influences the loading and unloading stages of gas, with the best results obtained at the lowest temperatures. In experiments involving mixtures of CH4, CO2 and H2, it was found that activated carbon has preferential adsorption by CO2 and desorption of CH4, so that under certain conditions this technology can be used to store gas and partially separate the components at the end of the process, capturing CO2 and delivering CH4 and H2 with greater purity. The storage of gas mixtures simulating biogas and biomethane proved to be the most advantageous due to the greater energy storage capacity per volume of gas. Finally, activated carbon was applied in equilibrium investigation from phenomenological models, it was verified that the adsorption models of Langmuir and Toth adequately described the experimental equilibrium data.